Nutritional quality of dietary patterns of children: are there differences inside and outside school? - Diva Aliete dos Santos Vieira; Michelle Alessandra Castro; Mauro Fisberg; Regina Mara Fisberg (Elsevier, 2017)
Objectives: To describe the dietary patterns of children inside and outside school and investigate their associations with sociodemographic factors and nutritional status. Methods: This was a multicenter cross-sectional study in which children of both sexes, aged 1-6 years, attending private and public daycare centers and preschools in Brazil, were evaluated (n = 2979). Demographic, socioeconomic and dietary data (weighed food records and estimated food records) were collected. Dietary patterns were derived by factor analysis from 36 food groups. Results: Four dietary patterns were identified inside school, and three outside. Inside school, the "traditional" pattern was associated to low income and presented high nutritional quality. The "dual" pattern was associated with low income and with high intake of added sugar and glycemic load. The "snack" pattern was associated with children enrolled at private schools and with high intake of added sugar and glycemic load. The "bread and butter" pattern was associated with high intake of added sugar and trans fat. Outside school, the "traditional" pattern was associated with high intake of saturated fat, trans fats, sodium, and total fiber. The "bread and butter" pattern was associated with high intake of trans fats and glycemic load, whereas the "snack" pattern was associated with overweight, private schools, high income, and high intake of trans fats, sodium, and total fiber. Conclusion: There are differences in the nutritional quality of dietary patterns inside and outside school, and heterogeneity in adherence to these patterns were observed across regions and socioeconomic classes. Resumo: Objetivos: Descrever os padrões alimentares de crianças dentro e fora da escola e investigar a sua associação com fatores sociodemográficos e estado nutricional. Métodos: Trata-se de um estudo multicêntrico transversal, no qual foram avaliadas crianças de 1 a 6 anos de ambos os sexos, atendidas em creches públicas e privadas e pré-escolas no Brasil (n = 2979). Foram coletados dados demográficos, socioeconômicos e dietéticos. Os padrões alimentares foram derivados por análise fatorial a partir de 36 grupos de alimentos. Resultados: Quatro padrões alimentares foram identificados dentro da creche e três fora da creche. Dentro da creche, o padrão "tradicional" foi associado a menor renda e apresentou melhor qualidade nutricional. O padrão "dual" associou-se a menor renda e maior ingestão de açúcar de adição e carga glicêmica. O padrão "lanches" foi associado a crianças matriculadas em escolas privadas e com maior ingestão de açúcar de adição e carga glicêmica. O padrão "pão com manteiga" associou-se a maior ingestão de açúcar de adição e gordura trans. Fora da creche, o padrão "tradicional" foi associado a maior ingestão de gordura saturada, trans, sódio e fibra. O padrão "pão com manteiga" associou-se a maior ingestão de gordura trans e carga glicêmica, enquanto o padrão "lanches" associou-se às crianças com excesso de peso, de creches privadas, maior renda e com maior ingestão de gordura trans, sódio e fibra. Conclusão: Houve diferença na qualidade nutricional dos padrões dentro e fora da escola e a aderência a esses ocorreu de forma heterogênea nas regiões e classes socioeconômicas. Keywords: Food consumption, Dietary patterns, Children, School feeding, Factor analysis, Palavras-chave: Consumo alimentar, Padrões alimentares, Crianças, Alimentação escolar, Análise fatorial